Share of Nations in 37 International Public Health Journals: An Equity and Diversity Perspective Towards Health Research Capacity Building - E de Leeuw; F Zaree; N Keshavarz Mohammadi; MM Emamjomeh (Tehran University of Medical Sciences, 2011)
Background: This paper contributes to further exploration of inequity in access to health research capacity development by examining the representation of different nations in international public health journals. It also aims to examine the degree of diversity that exists in these journals.Methods: This study is a descriptive survey. It was done with objective sampling on 37 ISI health journals on October of 2008.The number and nationality of people in different editorial positions of the journals was identified. The second analysis involved recalculating the numbers obtained for each nation to the population size of nations per million inhabitants. In order to better compare countries in terms of presence in editorial team of the journals, a 'public health editor equity gap ratio' (PHEEGR) was developed.Results: Low income countries have occupied none of the leadership positions of chief editor or associate /assistant chief editors and middle income countries at maximum shared less than 5 percent. The PHEEGR gap in access to the different editorial positions between highest to the lowest representation of countries was 16/1 for chief editors, 12/1 for associate editors , 335/1 for editorial boards and 202/1 for associate editorial boards. However, after normalizing the data to the country's population, the gap increased significantly.Conclusion: There is an imbalance and possibly even inequity in the composition of editorial boards and offices of international health journals that should be paid significant attention. This can contribute to fill the equity gap exists between health in developing and developed countries.